Influence of the test procedure for setting the external air movement on the thermal performance of open multideck display case - Heidinger, Gustavo Galdi (2014)
This paper reports the experimental results with an open multideck display case with dual air curtain. Manufacturers seek during the design phase of the equipment to certify its suitability to the testing standards with the lowest energy consumption and ensuring food safety. The testing standard ISO 23953 is usually followed to determine the equipment's thermal cooling load. However, some manufacturers use different procedures to set the external air velocity. The thermal cooling load will depend upon it. According to ISO 23953, the mean horizontal air velocity, with the refrigerated display case switched off, shall be 0.2 m/s. Thus, this paper reports the experimental results of tests where the initial procedure of setting the air velocity was performed by two different methods: (1) with the display case cooling on (2) and switched off as required by ISO 23953. The comparison of experimental results for the two conditions (switched off relatively to switched on) provide the quantitative variation of frost formation (-24%) and condensed water (+180%) on the evaporator coil and how this phenomena affects the distribution and magnitudes of air velocity (+7%); inlet (+5.9°C) and outlet temperatures (+5.5°C); the components of the total sensible (+10%) and latent (+15%) heat loads; and the average product temperatures (+176%). The analysis of experimental data provides the necessary basis to conclude that the initial procedure how the air movement is set affects significantly the performance of the equipment under testing. The results show that air movement procedure defined in the standard, although providing a higher thermal cooling load, is the most appropriated since the equipment will be able to operate correctly under more demanding ambient conditions and thus its design provides a better thermal performance.